Pytochemical profile and antioxidant activity of chiltepin chili (Capsicum annuum var. glabriusculum), Sonora, Mexico - Alvarez-Parrilla, Emilio (2020)
Quantification of chiltepin hot pepper (Capsicum annuum L. glabriusculum) phytochemicals provides a tool to evaluate the fruit quality and health impact. This study evaluates the phytochemical content and antioxidant activity of chiltepin from different locations of Sonora, Mexico, at two ripening stages (immature and mature). Seeds from Cumpas and Sahuaripa, were grown under greenhouse conditions and phenolic compounds, flavonoids, carotenoids, chlorophylls, and ascorbic acid were determined by spectrophotometric techniques. Capsaicinoids were determined by HPLC-DAD. The antioxidant activity was determined through DPPH and ABTS radical scavenging and by FRAP techniques. The origin of the seed influenced the antioxidant activity and phytochemical content. Samples from Cumpas, were superior in phytochemicals compared with Sahuaripa. Antioxidant activity and phytochemicals were higher in mature stage. Antioxidant activity correlates mainly with phenolic compounds and carotenoids. This study highlights that mature chiltepin pepper from Sonora could grow under controlled conditions develop bioactive compounds with antioxidant potential.